Antimyelin antibodies as predictors of disability after clinically isolated syndrome. (3rd August 2014) - Findling, Oliver; Durot, Isabelle; Weck, Anja; Jung, Simon; Kamm, Christian P.; Greeve, Isabell; Mattle, Heinrich P.; Sellner, Johann
<x xml:space="preserve">Abstract</x> There is controversy whether determination of antibodies against myelin, myelin oligodendrocyte glycoprotein, and myelin basic protein in serum from patients with a first episode suggestive of multiple sclerosis is of prognostic value. We evaluated whether detection of antimyelin antibodies in serum indicates a worse course with earlier time to a second relapse and increased progression of disability. We conducted a prospective study at the Department of Neurology, Inselspital Bern, Switzerland from 2004 to 2008 in patients presenting with a clinically isolated syndrome (CIS) and a follow-up of at least 4 months. Antimyelin antibodies were assessed by Western blot. Results were correlated with clinical course and sex. Among 93 consecutive patients with a CIS, 74 (80%) were positive for either one or both antimyelin antibodies. A relapse occurred in 49 (53%) and the median EDSS was 2 (range 1–3.5) after a mean observation period of 20 months. Presence of antimyelin antibodies at CIS neither increased the risk for a second relapse nor for progression of disability. Stratification for gender did not reveal differences for any of the clinical surrogates. The sole determination of antimyelin antibodies in serum is of limited prognostic value for the identification of patients with different short-term course.